Behavioral and Neurophysiological Study of Olfactory Perception and Learning in Honeybees - Sandoz, Jean-Christophe (Frontiers in Systems Neuroscience, 2011)
The honeybee Apis mellifera has been a central insect model in the study of olfactory perception and learning for more than a century, starting with pioneer work by Karl von Frisch. Research on olfaction in honeybees has greatly benefited from the advent of a range of behavioural and neurophysiological paradigms in the Lab. Here I review major findings about how the honeybee brain detects, processes, and learns odours, based on behavioural, neuroanatomical and neurophysiological approaches. I first address the behavioural study of olfactory learning, from experiments on free-flying workers visiting artificial flowers to laboratory-based conditioning protocols on restrained individuals. I explain how the study of olfactory learning has allowed understanding the discrimination and generalization ability of the honeybee olfactory system, its capacity to grant special properties to olfactory mixtures as well as to retain individual component information. Next, based on the impressive amount of anatomical and immunochemical studies of the bee brain, I detail our knowledge of olfactory pathways. I then show how functional recordings of odour-evoked activity in the brain allow following the transformation of the olfactory message from the periphery until higher-order central structures. Data from extra- and intracellular electrophysiological approaches as well as from the most recent optical imaging developments are described. Lastly, I discuss results addressing how odour representation changes as a result of experience. This impressive ensemble of behavioural, neuroanatomical and neurophysiological data available in the bee make it an attractive model for future research aiming to understand olfactory perception and learning in an integrative fashion.